The effect of alpha fetoprotein on NF-κB translocation in lipopolysaccharide induced monocyte-derived dendritic cell (Medical Journal of Indonesia, 2012)
Background: Alpha fetoprotein (AFP) is a tumor-associated Ag that has a function in both ontogenic and oncogenic growth and its serum level is elevated in patients with hepatocellular carcinoma (HCC). A recent study showed that the immunoregulatory effect of AFP was through impairment of dendritic cell function as antigen presenting cell (APC), a mechanism that is known to hamper efficient antitumor response. However, the underlying intracellular mechanism of action of AFP required elucidation. As an initial step to determine the signaling pathway of AFP, we analyzed whether LPS induced NF-κB translocation occured in AFP-treated monocyte-derived dendritic cell (MDDC), which was induced by lipopolysaccharide (LPS). Methods: Monocytes were cultured in GM-CSF (800 ng/mL) and IL-4 (1000 ng/mL) containing medium and incubated for six days to generate immature MDDCs with or without the presence of AFP. Mature MDDC was generated by stimulation of the immature MDDC with LPS for another 30 minutes. The analysis of NF-κB translocation was measured by fluorescent microscopy. Results: Following activation of MDDC by LPS, the control group showed a marked nuclear staining of NF-κB. However, the AFP-treated group showed negative nuclear staining similar as observed in unactivated MDDC. Conclusion: This study demonstrated that AFP prevented the activation and nuclear translocation of NF-κB and subsequently might cause the impairment of MDDC function as APC. This finding provides a new insight on the role of AFP in the suppression mechanism of anti tumor immune response. (Med J Indones. 2012;21:97-101)